Rapamycin Rescues the Poor Developmental Capacity of Aged Porcine Oocytes - Seung Eun Lee (Asian-Australasian Journal of Animal Sciences, 2014)
Unfertilized oocytes age inevitably after ovulation, which limits their fertilizable life span and embryonic development. Rapamycin affects mammalian target of rapamycin (mTOR) expression and cytoskeleton reorganization during oocyte meiotic maturation. The goal of this study was to examine the effects of rapamycin treatment on aged porcine oocytes and their in vitro development. Rapamycin treatment of aged oocytes for 24 h (68 h in vitro maturation [IVM]; 44 h+10 μM rapamycin/24 h, 47.52±5.68) or control oocytes (44 h IVM; 42.14±4.40) significantly increased the development rate and total cell number compared with untreated aged oocytes (68 h IVM, 22.04±5.68) (p<0.05). Rapamycin treatment of aged IVM oocytes for 24 h also rescued aberrant spindle organization and chromosomal misalignment, blocked the decrease in the level of phosphorylated-p44/42 mitogen-activated protein kinase (MAPK), and increased the mRNA expression of cytoplasmic maturation factor genes (MOS, BMP15, GDF9, and CCNB1) compared with untreated, 24 h-aged IVM oocytes (p<0.05). Furthermore, rapamycin treatment of aged oocytes decreased reactive oxygen species (ROS) activity and DNA fragmentation (p<0.05), and downregulated the mRNA expression of mTOR compared with control or untreated aged oocytes. By contrast, rapamycin treatment of aged oocytes increased mitochondrial localization (p<0.05) and upregulated the mRNA expression of autophagy (BECN1, ATG7, MAP1LC3B, ATG12, GABARAP, and GABARAPL1), anti-apoptosis (BCL2L1 and BIRC5; p<0.05), and development (NANOG and SOX2; p<0.05) genes, but it did not affect the mRNA expression of pro-apoptosis genes (FAS and CASP3) compared with the control. This study demonstrates that rapamycin treatment can rescue the poor developmental capacity of aged porcine oocytes.